Impact of combination antiretroviral therapy in the NOD.c3c4 mouse model of autoimmune biliary disease. (31st October 2014) - Sharon, David; Chen, Min; Zhang, Guangzhi; Girgis, Safwat; Sis, Banu; Graham, Don; McDougall, Chelsea; Wasilenko, Shawn T.; Montano‐Loza, Aldo; Mason, Andrew L.
Abstract Background & Aims The NOD.c3c4 mouse model develops autoimmune biliary disease characterized by spontaneous granulomatous cholangitis, antimitochondrial antibodies and liver failure. This model for primary biliary cirrhosis (PBC) has evidence of biliary infection with mouse mammary tumour virus (MMTV), suggesting that the virus may have a role in cholangitis development and progression of liver disease in this mouse model. We tested the hypothesis that MMTV infection is associated with cholangitis in the NOD.c3c4 mouse model by investigating whether antiretroviral therapy impacts on viral levels and liver disease. Methods NOD.c3c4 mice were treated with combination antiretroviral therapy. Response to treatment was studied by measuring MMTV RNA in the liver, liver enzyme levels in serum and liver histology using a modified Ishak score. Results Combination therapy with the reverse transcriptase inhibitors, tenofovir and emtricitabine, resulted in a significant reduction in serum liver enzyme levels, attenuation of cholangitis and decreased MMTV levels in the livers of NOD.c3c4 mice. Furthermore, treatment with the retroviral protease inhibitors, lopinavir and ritonavir, in addition to the reverse transcriptase inhibitors, resulted in further decrease in MMTV levels and attenuation of liver disease in this model. Conclusions The attenuation of cholangitis with regimens containing the reverse transcriptase inhibitors, tenofovir and emtricitabine, and the protease inhibitors, lopinavir and ritonavir, suggests that retroviral infection may play a role in the development of cholangitis in this model.